Pollution and biodiversity loss due to mining and agricultural activities: state of art - Paredes-Vilca, Oscar Junior (2024)
The services provided from biodiversity and ecosystems are endangered by the various activities carried out by human. Among them, mining and agricultural activities have contributed to the loss of biodiversity and deterioration of ecosystems, however the damage generated by mining is overshadowed by the economic benefits it brings. Thus, the objective of this study was to compile scientific literature that helps to determine the way in which these activities harm biodiversity and ecosystems, as well as the negative effects that they trigger between them. To do this, original and review articles from the Web of science, Scopus and Scielo databases were used. The findings show that there is contamination with heavy metals, a product of mining and the use of agrochemicals by agricultural activity. However, there are negative externalities generated in a unidirectional manner, with agricultural production being subject to the damage caused by mining.